The Effect of Product Quality and Price on Purchase Intention of Event Package at the Apurva Kempinski Bali - Arisanti, Putu Dea Oktavia; Diwyarthi, Ni Desak Made Santi; Witarsana, I Gusti Agung Gede (Formosa Journal of Applied Sciences, 2024)
The data analysis method used in this study is Multiple Linear Regression, Coefficient of Determination, t test and F test. According to the results of the study, it can be observed that product quality has a positive and significant impact on interest in buying event packages, prices have a significant positive effect on interest in buying event packages and product quality and prices, simultaneously have a significant impact on interest in buying event packages. The high impact of product quality variables and prices on buying interest in event packages is 65.2%. The input that can be conveyed by researchers is that it is hoped that The Apurva Kempinski Bali Hotel will evaluate the services provided, so that later it can provide more responsive services, evaluate the prices offered, always provide good service, maintain good product quality, and prices such as the benefits received by buyers.